Informal and nonformal learning for sport coaches: A systematic review - Walker, L. F.; Thomas, R.; Driska, A. P. (International Journal of Sports Science & Coaching, 2018)
Millions of athletes compete in sport for the enjoyment, physical, and psychosocial benefits that result from participation, and one of the most influential persons in creating a positive sport experience is the coach. As such, numerous sport governing bodies have instituted formal coach education programs, worldwide, over the past three decades. However, coaches most frequently learn, and often prefer to learn, from informal sources, as they tend to be contextually relevant and easily accessible. Given the pervasive nature of informal learning, the purposes of this systematic review were to: (a) examine the literature for themes and trends in sport context, methods, and means of informal and nonformal learning, and (b) illuminate gaps in the literature to inform the research field and coach educators. A total of 39 studies were examined for trends in publication, sport context, methods of inquiry, and themes in the sources and types of informal learning. The results show that: (1) research is spread widely across publications but not countries, (2) elite sport contexts are most frequently studied, (3) qualitative, cross-sectional methods are most frequently used, and (4) coaches learn informally through a variety of means; however, they are open to both interpersonal (coach-to-coach) or independent (knowledge search) means of learning. Future research should expand to include non-elite contexts, should employ greater methodological diversity, and should continue to explore the variety of preferred learning options.